Cytokine Receptor-Like Factor 3 (CRLF3) Contributes to Early Zebrafish Hematopoiesis - Taznin, Tarannum; Perera, Kaushalya; Gibert, Yann; Ward, Alister C.; Liongue, Clifford (Frontiers in Immunology, 2022)
Cytokine receptor-like factor 3 (CRLF3) is an ancient protein conserved across metazoans that contains an archetypal cytokine receptor homology domain (CHD). This domain is found in cytokine receptors present in bilateria, including higher vertebrates, that play key roles in a variety of developmental and homeostatic processes, particularly relating to blood and immune cells. However, understanding of CRLF3 itself remains very limited. This study aimed to investigate this evolutionarily significant protein by investigating its embryonic expression and function in early development, particularly of blood and immune cells, using zebrafish as a model. Expression of crlf3 was identified in mesoderm-derived tissues in early zebrafish embryos, including the somitic mesoderm and both anterior and posterior lateral plate mesoderm. Later expression was observed in the thymus, brain, retina and exocrine pancreas. Zebrafish crlf3 mutants generated by genome editing technology exhibited a significant reduction in primitive hematopoiesis and early definitive hematopoiesis, with decreased early progenitors impacting on multiple lineages. No other obvious phenotypes were observed in the crlf3 mutants.